The supersoft X-ray phase of nova RS Ophiuchi 2006 - Osborne, Julian P.; Page, K. L.; Beardmore, A. P.; Bode, M. F.; Goad, M. R.; O'Brien, T. J.; Starrfield, S.; Rauch, T.; Ness, J.-U.; Krautter, Joachim; Schwarz, G.; Burrows, D. N.; et al. (The astrophysical journal, 2011)
Swift X-ray observations of the ∼60 day supersoft phase of the recurrent nova RS Ophiuchi (RS Oph) 2006 show the progress of nuclear burning on the white dwarf (WD) in exquisite detail. First seen 26 days after the optical outburst, this phase started with extreme variability likely due to variable absorption, although intrinsic WD variations are not excluded. About 32 days later, a steady decline in count rate set in. NLTE model atmosphere spectral fits during the supersoft phase show that the effective temperature of the WD increases from ∼65 eV to ∼90 eV during the extreme variability phase, falling slowly after about day 60 and more rapidly after day 80. The bolometric luminosity is seen to be approximately constant and close to Eddington from day 45 up to day 60, the subsequent decline possibly signaling the end of extensive nuclear burning. Before the decline, a multiply-periodic ∼35 s modulation of the soft X-rays was present and may be the signature of a nuclear fusion driven instability. Our measurements are consistent with a WD mass near the Chandrasekhar limit; combined with a deduced accumulation of mass transferred from its binary companion, this leads us to suggest that RS Oph is a strong candidate for a future supernova explosion. The main uncertainty now is whether the WD is the CO type necessary for a Type Ia supernova. This may be confirmed by detailed abundance analyses of spectroscopic data from the outbursts.